PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN KOTA PALEMBANG UPTD BALAI PENGUJIAN KENDARAAN BERMOTOR - Irwana, M. Rizky; Roswaty, Roswaty; Handayani, Susi (Jurnal Ilmiah Ekonomi Global Masa Kini, 2018)
The aim of this study was find out the impact of motivation on employee performance at the Department of Transportation of Palembang City at UPTD of Commercial Vehicle Licensing Center. The data used was census data that takes all of fifty one employees as the sample. The technique for collecting the data was questionnaire. The result of the study conducted using empirical testing on a simple linear regression showed that Motivation (X) had an impact on the Performance (Y).The motivation to creating a good performance. Therefore, this company should be able to improve the motivation that will produce a maximum work. The results showed that there is a positive and significant influence between the motivation on employees performance.Motivation directly affected the employee performance in creating good performance. Thus employees should increase motivation in order to improve their performance. Finally, it could be concluded that there was a positive and significant impact of motivation on employee performance. Keywords:Motivation, Employee Performance, Human Resources Management